Influence of alkali metal cations on the formation of zeolites under hydrothermal conditions with no organic structure directing agents. Issue 12 (28th March 2015) - Nearchou, Antony; Sartbaeva, Asel
<x xml:space="preserve">Abstract</x> Alkali metal cations play an important role in directing formation of zeolite frameworks in the absence of organic structure directing agents.